The Effectiveness and Students’ Perceptions on Learning Tenses Through Mind Mapping Technique on Elementary Level at an Education and Training Institute in Indonesia - Nur Alifah Annisa Jumrah; Mirah Azizah (Hasanuddin University, 2021)
Numerous studies had conducted the use of mind mapping as a technique in teaching and learning English, but relatively few of these studies focused on the effectiveness and students’ perceptions of mind mapping technique in learning tenses on elementary level in a non-formal education institution. This study aimed to investigate the effectiveness of mind mapping technique in learning present tenses and students’ perceptions toward this technique on elementary level students of the English program. 30 students of the English program on elementary level at Aliah Education and Training Institute Makassar took part in the study. Data were collected through pre-test, post-test, observation, questionnaire, and interview and thus used to analyze the results quantitatively and qualitatively using preliminary studies, general mean scores, and percentages of students‘ improvement score. Results of the study showed that the students were really enthusiastic to learn with this technique and the atmosphere of the classroom was more enjoyable. In addition, the students’ ability in using tenses was improved after implementing this technique. In the pre-test, the general mean score of the students was 42.33 and classified as Very Poor. While, the general mean score of the students was 78.92 and classified as Good in the post-test. The students‘ improvement score was increased up to 86.44%. It revealed that mind mapping technique is effective in learning tenses. However, it is suggested that further studies can be conducted with larger data to make it more accurate and applicable.